MEMBANGUN PREKONOMIAN DESA MELALUI PENDIRIAN KOPERASI SYARIAH DI NTB (STUDI DI DESA RENSING BAT KECAMATAN SAKRA BARAT) - sani, zainus (Al-Hijrah: Journal of Islamic Economics And Banking, 2025)
The research aims to provide a solution to improve the economy of villages in NTB in the agricultural sector which have difficulty obtaining capital, and avoid interest-bearing debt which is a huge burden on the community by using the sharia system, namely profit sharing (mudharabah). This research uses qualitative research methods in Rensing Bat village, West Sakra sub-district, West Nusa Tenggara. by interviewing several sources such as Sharia Cooperative expert informants, this research used a purposive sampling technique, and analysis and decision making were carried out using the SWOT matrix approach. The results of this research are that the existence of the Sharia Cooperative provides great benefits for the people of Rensing Bat Village. Sharia cooperatives help people to be free from the practice of usury. Apart from that, the existence of Sharia Cooperatives also provides opportunities for local governments, because they can provide the best facilities to the community to overcome their economic problems through collaboration with Sharia Cooperatives. Even though there are risks and weaknesses in the Sharia Cooperative established in Rensing Bat Village, the advantages and opportunities possessed by the Sharia Cooperative are much more valuable. Based on the SWOT analysis, it can be concluded that the formation of a sharia cooperative in Rensing Bat village is.very important.